2016
DOI: 10.1007/s10120-016-0612-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of conventional endoscopy in the identification of submucosal invasion by early gastric cancer: the “non-extension sign” as a simple diagnostic marker

Abstract: Background and aim The ability to differentiate between mucosal (M) or microinvasive submucosal (SM1: depth of less than 500 lm) and invasive submucosal (SM2: depth of 500 lm or more) cancer is paramount when choosing the method of treatment for early gastric cancer (EGC). The ''non-extension sign'' relates to a localized increase in thickness and rigidity due to massive submucosal invasion by a cancer. The present study sought to assess the ability of conventional endoscopy (CE) to correctly identify SM2 canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 21 publications
0
50
1
2
Order By: Relevance
“…Non-magnified endoscopy is the primary modality for diagnosing gastrointestinal cancer, and is also helpful for diagnosing cancer invasion depth. Correlations between endoscopic macroscopic type and invasion depth of superficial EAC have been reported [31, 32], and previous studies showed that non-magnified endoscopy could accurately diagnose invasion depth in gastrointestinal cancers [3336]. One study found that the overall correct diagnostic assessment of early esophageal cancers was high using either non-magnified endoscopy or endoscopic ultrasonography (EUS) with a 20-MHz mini-probe, with no significant differences between the two techniques (Table 4) [37].…”
Section: Diagnosis Of Cancer Invasion Depthmentioning
confidence: 99%
“…Non-magnified endoscopy is the primary modality for diagnosing gastrointestinal cancer, and is also helpful for diagnosing cancer invasion depth. Correlations between endoscopic macroscopic type and invasion depth of superficial EAC have been reported [31, 32], and previous studies showed that non-magnified endoscopy could accurately diagnose invasion depth in gastrointestinal cancers [3336]. One study found that the overall correct diagnostic assessment of early esophageal cancers was high using either non-magnified endoscopy or endoscopic ultrasonography (EUS) with a 20-MHz mini-probe, with no significant differences between the two techniques (Table 4) [37].…”
Section: Diagnosis Of Cancer Invasion Depthmentioning
confidence: 99%
“…We believe that the non-extension sign could be considered a promising sign to evaluate invasion depth but today, application of this sign by its own is difficult in Western countries. First of all, the diagnostic accuracy showed in this study (80.3 %) did not reach the accuracy of the original study (96.9 %) [4]. The authors tried to explain that difference, saying that the first study was a real-time study, while this was only based on images.…”
mentioning
confidence: 55%
“…The non-extension sign is a diagnostic criterion proposed by Nagahama et al [4] which, when the gastric wall is well distended by endoscopic air insufflation, consists of a protrusion of surrounding mucosa into the lumen, resembling a trapezoidal shape. This is used to define the invasion depth of EGC as T1b2 carcinoma and showed an accuracy of 96.9 %.…”
mentioning
confidence: 99%
“…Endoscopic features of EGCs in all cases showed a attened and extended appearance when the entire stomach wall was distended with a high volume of air. Therefore, patients were diagnosed with intramucosal gastric cancer because they were negative for the nonextension sign [12]. Three cases (case1, 3, 4) had none atrophic mucosa around EGC.…”
Section: Submucosal Invasive Early Gastric Cancer In the H Pylori-egmentioning
confidence: 99%